In-vitro Comparative Antioxidant Activity of Ethanolic Extracts of Glycosmis pentaphylla and Bauhinia variegata - Kinja K1, Shailesh S1, Bhatia L2*, Bishnoi H1, Chauhan P1 (Recent Research in Science and Technology, 2011)
This study was conducted to investigate the antioxidant effect of the ethanolic extracts of the leaves of Glycosmis pentaphylla and Bauhinia variegata. The antioxidant activity was evaluated by various antioxidant assays, including 1, 1-diphenyl-2-picrylhydrazyl (DPPH), 2, 2’-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) (ABTS), nitric oxide and hydrogen peroxide (H2O2) scavenging method. The antioxidant activities were compared to standard antioxidant ascorbic acid. Ethanolic crude extract of the plant Leucas aspera showed maximum significant antioxidant activity in DPPH, ABTS, nitric oxide and H2O2 scavenging methods. The findings of the present study suggested that these two plants could be a potential natural source of antioxidants and could have greater importance as therapeutic agent in preventing or slowing oxidative stress related degenerative diseases.